Cyp1A and ABC transporter expression and function in PLHC-1cell line after microcystin-LR and Benzo (a)pyrene exposure - Bieczynski, Flavia (2025)
The dataset presented corresponds to a study investigating mixture toxicity between two common aquatic contaminants, microcystin-LR (MCLR) and benzo[a]pyrene (BaP), on the detoxification system of fish. We used the Poeciliopsis lucida hepatocellular carcinoma (PLHC-1) cell line as a model for fish liver cells. The data was collected from May 2022 to August 2024. Cells were exposed to MCLR (0.01, 1 µM), BaP (0.01, 0.1, 1 µM), or combinations of both chemicals for periods ranging from 1 to 48 hours. We measured the following endpoints: - Cytochrome P450 1A (CYP1A) function and regulation, assessing ethoxy resorufin-O-deethylase (EROD) activity and CYP1A mRNA expression. EROD activity was normalized to the protein. - P-glycoprotein (Pgp) function and expression, using the rhodamine 123 (Rh123) accumulation assay and Pgp mRNA expression. Rh123 accumulation was normalized to the protein. - Cell cytotoxicity, using two fluorescent indicators, 5-Carboxyfluorescein Diacetate-Acetoxymethyl Ester (CFDA-AM) and Alamar Blue (AB).